Safety, Tolerability and Pharmacokinetics of the Serotonin 5-HT6 Receptor Antagonist, HEC30654, in Healthy Chinese Subjects - Li, Xiaojiao; Gao, Lei; Liu, Jingrui; Zhang, Hong; Chen, Hong; Yang, Lizi; Wu, Min; Li, Cuiyun; Zhu, Xiaoxue; Ding, Yanhua; Sun, Li (Frontiers in Pharmacology, 2021)
Background and Objective HEC30654 is a selective 5-HT6 receptor antagonist that was safe and well-tolerated in preclinical models of Alzheimer’s disease. The objective of this double-blind, randomized, placebo-controlled clinical trial was to evaluate the safety, tolerability, and pharmacokinetic profile of HEC30654 after single ascending doses in healthy Chinese subjects. Methods Healthy volunteers received a single oral dose of HEC30654 (5, 10, 15, 30, 60 mg). Safety and tolerability assessments included adverse events, vital signs, and findings on electrocardiograms, electroencephalograms, physical examination, and clinical laboratory tests. Pharmacokinetic analysis of HEC30654 and its major metabolite HEC93263 were conducted in blood, urine, and fecal samples. Results Single doses of HEC30654 up to 30 mg were generally safe and well tolerated, but dose escalation was terminated early as the 60 mg HEC30654 treatment group met the pre-defined stopping rules specified in the protocol. Median tmax of HEC30654 was 6 h (range, 4-12 h), t1/2 of 10-60 mg HEC30654 ranged from 52.1-63.8 h. Exposure to HEC30654 across the dose range explored in this study increased more than in proportion to dose. Metabolism of HEC30654 to HEC93263 was slow (<10%), and HEC30654 was mainly eliminated unchanged through feces. Conclusions Single doses of HEC30654 up to 30 mg were generally safe and well tolerated. Based on preclinical efficacy in various models of cognition, HEC30654 may represent a therapeutic option for symptomatic treatment of cognitive disorders.